116 Knowing what Older Adults Want: A Soft Service Robot in Object Retrieval Tasks. (20th December 2019) - Lee, Loong Yi; Hossen, Ismaiil S; Syadiqeen, Omar Ali; Teh, Pei-Lee; Tan, Chee Pin; Nurzaman, Surya G
Abstract: Introduction: An ageing society in this period of technological development may benefit from having service robots assist them in daily tasks. To that end, service robots that are equipped with soft grippers have the potential to handle the unstructured nature of objects such as eye-glasses and cutlery at homes. Drawing from Technology Acceptance Model, this paper aims to analyse technology adoption of a "soft service robot" for object retrieval tasks among older adults. Method: A video demonstrating the operational functions of an in-house developed soft service robot was shown to 30 participants aged 60 and above. The video shows that the soft service robot can be remotely controlled through the internet to move around and pick up various household objects delicately. The soft service robot also enables users to interact with another individual through an integrated tablet. Thirty participants completed a survey measuring perceived ease of use, perceived usefulness, attitude towards the soft service robot and behavioural intention using seven-point Likert scales. Multiple regression analysis was performed to test the hypothesized model. Results: Our study showed that the behavioral intention of older adults was jointly determined by the perceived usefulness (β=0.401; p-value< 0.01) and the attitude of the older adults towards the soft service robot (β=0.530; p-value<0.01). Interestingly, this study found a non-significant perceived ease of use-intention relationship (β=-0.167; p-value>0.05) in the model. Conclusion: Our findings indicated that making a soft service robot easier-to-use has little or no impact on the formation of intentions. Essentially, a soft service robot that is perceived to be useful will be accepted by older adults. From a practical standpoint, it is of significant importance for service robotics designer and developers to build soft service robot with useful functions to enhance greater adoption of such technology among older adults.